The 'Betrieb' as Corporate Actor: management revue. Socio-Economic Studies - Matiaske, Wenzel; Alewell, Dorothea; Leßmann, Ortrud (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
Organisations and their establishments are often said to ‘act’ as if they were people, but to what extent does this analogy hold true? Do they act as collective actors? How does that work? Who plays what role in this respect? Can corporate actors be held to account? These philosophical questions have practical relevance in the context of firms and their establishments. In Germany, firms’ establishments are the subjects of labour law and other regulations and are called ‘Betriebe’. This volume comprises sociological and political analyses of organisations and their divisions and members, and discusses the legal and normative status of organisations as corporate actors.With contributions byDorothea Alewell, Ortrud Leßmann; Lutz Bellmann; Rolf Brühl; Cécile Ezvan, Cécile Renouard; Arne Kalleberg; Berndt Keller; Hartmut Kliemt; David Marsden; Albert Martin; Wenzel Matiaske; Wolfgang Mayrhofer; Dieter Sadowski; Frank Schirmer; Charlotte Schmidt-Leonardy; David P. Schweikard and Bénédicte Zimmermann.